2013
DOI: 10.11111/jkana.2013.19.4.462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-leadership and Job Involvement on Clinical Competence in General Hospital Nurses

Abstract: Purpose: This study was performed to identify the effects of self-leadership and job involvement on clinical competence in general hospital nurses. Methods: The participants in this study were 443 staff nurses working in general hospitals and having more than 6 months of nursing experience. Data were collected using self-administered questionnaires. Results: There were significant positive correlations between nurses' self-leadership and job involvement, and between nurses' self-leadership and clinical compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 12 publications
0
8
2
3
Order By: Relevance
“…In addition, they had higher competence scores on attitudes towards nursing care than on the other subfactors of clinical competence, and lower scores on competence in providing nursing care than on other subfactors. Notably, our participants' scores were lower than those in previous studies using the Clinical Competence Instrument [17], which reported high mean scoresdspecifically, 4.10 and 4.18 [1,4]don competence in providing support to patients and competence in providing nursing care, respectively. These differences from previous studies [1,4] may be attributable to differences in the participants' characteristics.…”
Section: Q2contrasting
confidence: 83%
See 1 more Smart Citation
“…In addition, they had higher competence scores on attitudes towards nursing care than on the other subfactors of clinical competence, and lower scores on competence in providing nursing care than on other subfactors. Notably, our participants' scores were lower than those in previous studies using the Clinical Competence Instrument [17], which reported high mean scoresdspecifically, 4.10 and 4.18 [1,4]don competence in providing support to patients and competence in providing nursing care, respectively. These differences from previous studies [1,4] may be attributable to differences in the participants' characteristics.…”
Section: Q2contrasting
confidence: 83%
“…Notably, our participants' scores were lower than those in previous studies using the Clinical Competence Instrument [17], which reported high mean scoresdspecifically, 4.10 and 4.18 [1,4]don competence in providing support to patients and competence in providing nursing care, respectively. These differences from previous studies [1,4] may be attributable to differences in the participants' characteristics. Specifically, participants in similar studies had higher levels of education and longer periods of work experience, which may have increased nurses' confidence in their clinical competence [22].…”
Section: Q2contrasting
confidence: 83%
“…또 한 프리셉터의 핵심역량은 신규간호사 중 프리셉터와 갈등을 경험하지 않은 집단에서 더 높은 수준으로 평가되어 (Kim & Kwon, 2007) (Park, 2008), 간호사의 비판적 사고성향과 업무수행 능력과도 관계가 있으며 (Kang, Kim, & Ryu, 2011;Sung & Eum, 2009), 직무만족과도 관계가 있었다 (Sung & Eum, 2009 (Manz, 1983). 간호사의 셀프리더십은 임상수행 능력 (Han & Park, 2013), 직무만족 (Han & Park, 2013), 조직 몰입 (Rubin, Martin, Bruning, & Power, 1991 (Rubin et al, 1991), 프리셉터의 역할과 기능을 잘 해내기 위해서는 사람을 대하는 의사소통 기술이 무엇보 다 중요한 역량 중 하나이다 (Im & Kim, 2008 The Effects of Self-efficacy, Critical Thinking Disposition, Self-leadership, and Communication Competency on the Core Competencies of the Preceptor in Advanced General Hospitals…”
Section: 프리셉터십은 프리셉터가 신규간호사의 교육을 담당하면서unclassified
“…In addition, it is worth mentioning that nursing competence varies depending on the type of sector (13)(14) .…”
Section: Discussionmentioning
confidence: 99%